A bazaar assemblage: reconstructing consumption, production and trade from mineralised seeds in Abbasid Jerusalem. (18th February 2019) - Amichay, Oriya; Ben-Ami, Doron; Tchekhanovets, Yana; Shahack-Gross, Ruth; Fuks, Daniel; Weiss, Ehud
Abstract: Abstract : Recent excavations in the historic centre of ancient Jerusalem have revealed evidence of an Abbasid (eighth- to tenth-century AD) marketplace. Refuse pits and cesspits have yielded an exceptionally well-preserved archaeobotanical assemblage—the first to be recovered from a Levantine marketplace, and the first in the region to be almost entirely preserved by mineralisation. Among several rare species identified is the earliest discovery of aubergine in the Levant. The assemblage includes staple and luxury food plants, medicinal herbs and plants used for industrial production, illuminating patterns of consumption, production, trade and the socioeconomic structure of Abbasid Jerusalem.